Mengkritisi Teori Pembangunan Ekonomi Konvensional - M. Shabri Abd. Majid (Share: Jurnal Ekonomi dan Keuangan Islam, 2012)
The failure of western economists to identify the factors that cause of the differences in economic growth within a country over time and differences in economic growth between countries are because of their weaknesses and ignorance. Besides, the ignorance of the role of science in the early emergence of the theory of economic development, until now they still deny the presence of the grace of Allah SWT as the most important factor causing the ongoing economic development of the people. Because of the high value of science in Islam, then the mastery of science comprehensively and completely will allow Muslims to build its economy. However, economic development of the people will never apply without the blessing of Allah through His grace stream. This paper is to review and uncover the weakness of western economic growth theory since the theory was first initiated. Although, initially the western economists had ignored the role of science as one important indicator of economic development, then in the end of 2nd millennium they have a mastery of knowledge is absolutely necessary to develop the economy of the country. It is clearly shows that, finally the western economists were forced to admit the truth of the words of Allah that has been poured in the Muslim holy book, Al Qur'an, about the importance of the role of sciences in life in this world. ABSTRAK - Kegagalan para ahli ekonomi barat untuk mengidentifikasi faktor-faktor penyebab terjadinya perbedaan pertumbuhan ekonomi dalam sebuah negara dari masa ke masa dan perbedaan pertumbuhan ekonomi antar negara adalah mutlak disebabkan oleh kedhaifan dan kejahilan mereka sendiri. Selain sempat mengabaikan peran ilmu pengetahuan pada awal-awal kemunculan teori pembangunan ekonomi, hingga detik ini mereka masih menafikan kehadiran rahmat Allah SWT sebagai faktor terpenting penyebab berlangsungnya pembangunan ekonomi umat. Karena tingginya nilai ilmu pengetahuan dalam Islam, maka penguasaan ilmu pengetahuan secara komprehensif dan benar jelas akan memudahkan umat Islam untuk membangun ekonominya. Namun, pembangunan ekonomi umat tidak akan pernah berlaku tanpa mendapat restu Allah SWT melalui cucuran rahmatNya. Tulisan ini meninjau dan menguak kedhaifan teori pertumbuhan ekonomi barat sejak teori itu pertama kali digagaskan. Walaupun pada awalnya para ahli ekonomi barat sempat mengabaikan peran ilmu pengetahuan sebagai salah satu indikator penting dalam pembangunan ekonomi, namun di akhir milineum ke-2 mereka telah menyadari bahwa penguasaan ilmu pengetahuan adalah mutlak diperlukan untuk membangun ekonomi negara. Ini, secara jelas, menunjukkan bahwa, akhirnya, para ahli ekonomi barat terpaksa mengakui kebenaran kata-kata Allah SWT yang telah dituangkan dalam kitab suci umat Islam, al-Qur’an tentang pentingnya peran ilmu pengetahuan dalam menjalani kehidupan di dunia fana ini.